2010
DOI: 10.1007/s11547-010-0561-9
|View full text |Cite
|
Sign up to set email alerts
|

Utility of second-look ultrasound in the management of incidental enhancing lesions detected by breast MR imaging

Abstract: Second-look US is a reliable problem-solving tool in identifying and characterising most incidental MRI findings. It contributes to accurately selecting the cases in which MRI-guided biopsy is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 25 publications
5
32
1
1
Order By: Relevance
“…This in agreement with Nothacker et al, [13] with a summarized cohort study on the role of ultrasound in the framework of malignant cancer screening. Our observations are parallel with Abe et al [14] in which not all breast masses were declared cancerous. Ultrasound is blamed for many wrong diagnoses in confirmed (earlier termed: suspicious) masses.…”
Section: Breast Sonogram Comparison On Both Types (Benign and Malignasupporting
confidence: 92%
See 1 more Smart Citation
“…This in agreement with Nothacker et al, [13] with a summarized cohort study on the role of ultrasound in the framework of malignant cancer screening. Our observations are parallel with Abe et al [14] in which not all breast masses were declared cancerous. Ultrasound is blamed for many wrong diagnoses in confirmed (earlier termed: suspicious) masses.…”
Section: Breast Sonogram Comparison On Both Types (Benign and Malignasupporting
confidence: 92%
“…It should be noted that ultrasound sometimes affirms MRI findings in breast cancer thereby demonstrating obscure lesions of BI-RADS grade 3 and 2 as stated by Carbognin et al when suspicion level in high. [4] Irrespective of were the masses are located, recommendation of mastectomies is left for general surgeons, beyond the scope of this review. 2 Criteria for ultrasound breast mass identification II BI-RADS [5] criteria employed in classification was obtained from evidence based on frozen sonograms.…”
Section: Resultsmentioning
confidence: 99%
“…As reported by other studies [17][18][19][20], second-look US is the fi rst reasonable approach for identifying and characterising lesions incidentally detected on MR imaging. In our series, second-look US resolved the management of a large majority (73%) of MR-visible lesions, a percentage higher than reported in other studies [17,18].…”
Section: Discussionmentioning
confidence: 75%
“…This requires not only to be familiar with (supine) breast US but also with (prone) breast MRI as well as with the different lesion location at the two imaging techniques. Six recent studies reported percentages of US correlate for initially MR-detected findings variable from 46% to 82% [17][18][19][20][21][22]. Pooling their results, we have a total of 1,208 findings, 759 of them with a US correlate (63%).…”
Section: Additional Findings At Preoperative Mri a Simple Golden Rulmentioning
confidence: 89%